Design and build a web-based guitar inventory system - Oktia Dwi Hapsari; Murti Retnowo (Jurnal Mantik, 2023)
With the rapid technological developments, many companies continue to make efforts and strategies to survive in their business. The role of company in managing the availability of goods (inventory) is one of the success factors for a company to maintain its business. Therefore, the customers demand can fulfill their requests as much as possible. Almoon's Guitar Gombong shop uses a manual recording system. The shortcomings of the current manual system include inefficiency in terms of time to find out the stock of goods when consumers arrive. In addition, the calculation of incoming goods data and outgoing goods data is still manual, which may result in errors or inaccuracies in the calculations, hampering the store performance. In the report that is required to be submitted to the leadership, it will take a long time and there is even a possibility that the archive will be lost or damaged. Therefore, the researchers aim to create a system to make it easier to collect data on goods, with the hope that the system will facilitate the work at Almoon's Guitar Store in managing inventory. The inventory system designed in this project can manage incoming and outgoing goods data as well as stock data in one web-based application.